2018
DOI: 10.3389/fneur.2018.00548
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Outcome, and Predictors of Intracranial Hemorrhage in Adult Patients on Extracorporeal Membrane Oxygenation: A Systematic and Narrative Review

Abstract: Background: Intracranial hemorrhage (ICH) is a common complication in adults treated with extracorporeal membrane oxygenation (ECMO).Objectives: The aim of this study was to conduct a systematic review of the literature on the incidence, outcome and predictors of ECMO-associated ICH in adult patients, supplemented by a narrative review of its pathophysiology, management and future perspectives.Methods: MEDLINE, EMBASE, Cochrane Database of Systematic Reviews and www.clinicaltrials.gov were systematically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 92 publications
4
67
2
Order By: Relevance
“…A systematic literature review suggested incidence of intracranial hemorrhage between 1.8-21% during veno-venous or veno-arterial ECMO. (21,22) ICU survival in our cohort (52.8%) is lower than reported by other data for severe ARDS (38%). (23) Our registry contains severely ill patients as suggested by the predicted mortality of 50.0% according to the SOFA score (24), which might explain these differences.…”
Section: Intracerebral Hemorrhages and Ardscontrasting
confidence: 69%
“…A systematic literature review suggested incidence of intracranial hemorrhage between 1.8-21% during veno-venous or veno-arterial ECMO. (21,22) ICU survival in our cohort (52.8%) is lower than reported by other data for severe ARDS (38%). (23) Our registry contains severely ill patients as suggested by the predicted mortality of 50.0% according to the SOFA score (24), which might explain these differences.…”
Section: Intracerebral Hemorrhages and Ardscontrasting
confidence: 69%
“…ICH is the most severe bleeding complication in patients on ECMO, with a mortality rate of 32 to 100%. 95,96 According to the 2019 ELSO registry data, incidence of ICH is 6 to 15% in pediatric patients compared with 2 to 4% in adults. The underlying mechanisms of hemorrhagic diathesis are still not completely understood due to the complexity of underlying disease-related factors and ECMO-related factors.…”
Section: Intracranial Hemorrhagementioning
confidence: 99%
“…The circuit volume of an ECMO circuit is large volume relative to the total blood volume of neonates, giving the priming fluid in ECMO circuits a larger influence on the hematologic status of the patient 78,79 . Neonatal patients have increased rates of intracranial hemorrhage compared to adults, with rates up to 16%‐34% compared to 2%‐21% for adults 7,80‐84 . Neonatal ECMO survivors below 2 kg have been reported, although this population has an increased complication rate, including intracranial hemorrhage, and increased mortality 85 …”
Section: Neonatal Versus Pediatric Versus Adult Ecmomentioning
confidence: 99%